Immunological and autonomic profile of ischemic stroke in lowlands - Nargiza T. Chekeeva; Svetalana G. Shleifer; Bolot B. Kulov; Begimai B. Kadyrova; Asel T. Jusupova; Elena V. Andrianova (Heart Vessels and Transplantation)
Introduction: Ischemic stroke (IS) accounts for 80–92% of all stroke cases and is primarily associated with cardiovascular diseases and chronic cerebral ischemia. Stroke severity is influenced not only by the localization and volume of the ischemic focus but also by the degree of autonomic-vascular and neuroinflammatory changes. Investigating the relationship between immune and autonomic system parameters in IS, particularly concerning disease severity, remains a crucial area of research.